Industrial application of supercritical carbon dioxide soluble polymers - Castanon-Rodriguez, Alba (2019)
Carbon capture has become a major global process, carbon dioxide (CO2) can be separated as a by-product in the industrial production of ammonia and ethanol using different methods such as cryogenic separation or the use of membranes, reducing the carbon footprint of the process.